Iatrogenic chlorpromazine abuse in a kitten - Gülersoy, Erdem (Array, 2020)
Chlorpromazine is a sedative effective phenothiazine derivative used to prevent nausea and vomiting, especially in cases of motion sickness in cats. It has serious side effects at high doses, including weakness, tremors, loss of anal sphincter tone and reflexes, hypotension, heart rhythm abnormalities, coma, agitation and seizures. In this case report, chlorpromazine toxicity was defined in a 4-month-old, 1.2 kg male Van kitten brought to Selcuk University Veterinary Faculty Emergency Clinic with complaints of stagnation, tremors, vomiting and excessive sleepiness. Hypothermia (35.2 °C), hyperpnea (88 breaths/min), hypersalivation, constipation, excessive agitation, tremors and incoordination were determined in the clinical examination of the kitten. It was learned from the anamnesis that 100 mg chlorpromazine was given orally before the trip against motion sickness. Electrocardiographic examination determined sinus tachycardia (220 beats/min), increase in P wave amplitude, elevation in ST complex and hypotension (S/MAP/D = 148/124/112). The major laboratory findings were metabolic acidosis (pH 7.278), hypoglycaemia (61 mg/dL), leukocytosis (22.43 m/mm3), increase in blood ured nitrogen (17.7 mg/dL), creatinine (0.6 mg/dL) and ALP (121 U/L) concentrations and hypertriglyceridemia (122 mg/dL). Based on the anamnesis, clinical, laboratory and ECG findings, the kitten was diagnosed with overdose chlorpromazine toxicity and hospitalized, and put under surveillance for continuous cardiac monitoring. Lactated ringer solution, norepinephrine tartrate, furosemide, activated charcoal and oxygen therapy were given. The treatment was successful. In conclusion, it was evaluated that continuous cardiac monitoring and controlling hypotension were important in the management of chlorpromazine toxicity, and fluid therapy, norepinephrine, diuretic and activated charcoal administrations achieve success in treatment.